Quantitative assessment method for firefighting danger based on numerical simulation of forest fire spread in canyon wind fields. - Ao Wang; Chenghu Wang; Guiyun Gao; Ningyu Wu; Haiyan Su (PLoS ONE, 2025)
Forest firefighting incidents frequently occur in mountainous and canyon regions which are characterized by complex topography, primarily because of variable local wind patterns that create conditions conducive to the spread of forest fires. This study focuses on the Muli forest fire in Liangshan Prefecture, which occurred on March 28, 2020. The WindNinja modeling software was utilized to simulate the valley wind field, whereas FARSITE modeling software was used to assess the fire spread rate, fireline intensity, and flame length. Moreover, a comprehensive forest firefighting risk assessment model was developed, incorporating factors such as forest fire behavior, fuel types, topography, and vulnerability indices. This model examines the analysis of risk variations across different topographical features and vegetation types. The analytic hierarchy process was employed to determine the weight of each index. Based on the numerical modeling data of forest fire behavior, it was found that the proportion of areas with high and perilous spreading rates in the study area was 16% and 54%, respectively. Areas exhibiting highly and extremely dangerous fireline strengths comprised 5.9% and 0.14%, respectively. Furthermore, the proportion of areas with highly and extremely dangerous flame lengths was 21% and 8.1%, respectively. The average firefighting danger index for grassland was 11, which is the highest among the five forest vegetation types, (evergreen broadleaf forests, evergreen coniferous forests, deciduous broadleaf forests, grasslands, and shrublands), whereas the average danger indices for deciduous broadleaf forest and evergreen coniferous forest were 10.3 and 7.4, respectively. The comprehensive assessment results indicated that 16.5% and 21.4% of the study area face high and extremely high firefighting danger levels, respectively. The comprehensive firefighting danger index for grassland was the highest among all vegetation types in the research area, thereby identifying it as a critical zone for preventing firefighting casualties and implementing countermeasures.